Komunikasi Publik Kebijakan Haji dalam Ekosistem Media Digital: Studi Kasus Tata Kelola Informasi Kementerian Haji - Abdul Rahman Syahputra; Hasan Sazali (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze Hajj policy communication within the digital media ecosystem, strategies for pilgrim information services, information crisis management and public communication transparency, as well as the relationship between the state and religion in religious public services. The research employs a qualitative approach using library research and a case study perspective. Data were collected from scholarly journals, books, policy documents, and reports from relevant international organizations, and subsequently analyzed through content analysis and thematic analysis. The findings indicate that digital media play a significant role in enhancing the effectiveness of Hajj policy communication by providing information that is faster, more accessible, and more responsive. Effective information service strategies are characterized by the integration of information systems, the utilization of digital technology, and communication that is oriented toward the needs of pilgrims. Information crisis management and public communication transparency are essential factors in maintaining public trust in the administration of Hajj services. Furthermore, the relationship between the state and religion in religious public services is increasingly strengthened through digital governance that promotes transparency, participation, and accountability. This study emphasizes that policy communication and digital governance constitute fundamental pillars in realizing effective Hajj administration that is centered on the needs and services of pilgrims